The Degree of Practicing Teachers of the First Cycle of the Competencies Necessary for them (Field Study In Basic Education Schools In Lattakia City) - Ali , Wafica Salman; Zreiki, Hyam Sadik; Gazzolin, Kinana Khaled (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research aimed to identify the practice level of the first unit teachers to the performance skills, from the point of schools' managers view in Lattakia city, by using notice card. Descriptive method has used to achieve this aimed, the study included (29) managers and (29) teachers from both genders from elementary schools in Lattakia city for (2017/2018) academic year. Questionnaire to the performance skills was provided and included three issues: (planning, implementation and evaluation) and consisted of (46) points, as well as a note card for teachers, contained the same fields. Reached had several results, the most important of which: -The degree of practice of the teachers of the of the first cycle of basic education of performance competencies from the point of view of managers in the city of Lattakia came to a high degree. -The degree of practicing teachers in the first seminar in the city of Lattakia for performance competencies according to note card came to a medium degree. -There are statistically significant differences between the scores of the members of the research sample on the observation card to assess the degree of their exercise of the performance competencies according to the variable of the educational qualification diploma campaign .While there was no statistically significant difference according to variable number of experience. -There was a statistically significant difference between the average grades of principals of basic education schools and the grades of teachers of the first cycle of basic education in Lattakia on the note card on the degree of exercise of competencies in the performance of the answers of managers. The study also made recommendations, including training courses for teachers of basic education before joining the teaching profession, and setting up special workshops for teachers to train them in practice on the performance competencies, which showed the results of the low degree of practice.